2013
DOI: 10.1097/mca.0b013e32835bbe6e
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of γ-glutamyltransferase and progression of coronary atherosclerosis

Abstract: ΔGGT2-1 is associated with angiographic coronary ATS progression in patients with ischemic heart disease on statin treatment, suggesting that oxidative stress may be another therapeutic target for preventing ATS progression beyond that of lipid-lowering therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…[7][8][9] More severe and diffuse coronary lesions have a worse prognosis in patients with CAD. [10][11][12] Extent severity and complexity of CAD in patients presenting with STEMI and possible correlations between serum GGT activities have not been adequately studied. Therefore, we evaluated the relationship between GGT activity and the burden of CAD as assessed by SYNTAX score (SXscore) in patients with STEMI.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] More severe and diffuse coronary lesions have a worse prognosis in patients with CAD. [10][11][12] Extent severity and complexity of CAD in patients presenting with STEMI and possible correlations between serum GGT activities have not been adequately studied. Therefore, we evaluated the relationship between GGT activity and the burden of CAD as assessed by SYNTAX score (SXscore) in patients with STEMI.…”
Section: Introductionmentioning
confidence: 99%
“…6 γ-Glutamyl transferase (GGT), a plasma membrane enzyme responsible for the extracellular catabolism of glutathione, is a marker of oxidative stress 7 and may directly take part in atherogenesis. 8 Previous studies have also showed the importance of oxidative stress in the development of endothelial dysfunction in patients with Behçet disease. 9,10 These findings have led us to the hypothesis that since the potential frequency of endothelial dysfunction and early atherosclerosis might be higher in Behçet disease, characterized by acute and chronic inflammatory attacks, it may lead to impairment in flow-mediated dilatation and an increase in epicardial adipose tissue thickness.…”
mentioning
confidence: 99%
“…Reduced flow‐mediated dilatation is also an early marker of atherosclerosis and has been indicated to predict future cardiovascular disease events 6 . γ‐Glutamyl transferase (GGT), a plasma membrane enzyme responsible for the extracellular catabolism of glutathione, is a marker of oxidative stress 7 and may directly take part in atherogenesis 8 . Previous studies have also showed the importance of oxidative stress in the development of endothelial dysfunction in patients with Behçet disease 9 , 10 …”
mentioning
confidence: 99%
“…Furthermore, serum concentrations of GGT and its activity are correlated with the intensity of the presence of metabolic risk factors, calci cation of coronary arteries, stiffness of their walls, and stenosis and predict the progression and severity of the disease. Additionally, serum levels of GGT are a prognostic marker for CAD, and alone or along with other markers, it could determine the mortality and morbidity following CAD [43][44][45][46][47][48][49]. Shabbir et al [5] studied the levels of 218 adults aged < 45 years, out of which 111 had CAD.…”
Section: Discussionmentioning
confidence: 99%